2006
DOI: 10.1021/ja066870j
|View full text |Cite
|
Sign up to set email alerts
|

Radically Different Antioxidants:  Thermally Generated Carbon-Centered Radicals as Chain-Breaking Antioxidants

Abstract: A new class of thermally activated chain-breaking antioxidants is presented. Dimers of persistent carbon-centered radicals are able to inhibit the autoxidation of cumene and styrene with better rate constants than the commercial antioxidant Irganox HP-136 and 3,5-di-tert-butyl-4-hydroxyanisole. A dramatic increase in antioxidant activity is observed with increasing temperature as more dimers dissociate to their corresponding persistent radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 13 publications
2
58
0
1
Order By: Relevance
“…Thework of Cheng and co-workers supported this observation because the molar mass of polystyrene calculated from SEC decreased by freezing the solution but recovered by heating to 100 8 8C. [37][38][39] Because of these distinctive properties,t his radical system enables in situ quantitative evaluation of polymer chain scission through electron paramagnetic spectroscopic (EPR) studies,u nlike previously reported mechanophores. [31,32] These studies suggest that freezing polymer solutions does not generate polymer chain scission but conformational changes.T herefore,w hether freezing polymer solutions actually induces mechanical force along the polymer chains and if so,t he magnitude of the force generated, remains unclear.…”
mentioning
confidence: 99%
“…Thework of Cheng and co-workers supported this observation because the molar mass of polystyrene calculated from SEC decreased by freezing the solution but recovered by heating to 100 8 8C. [37][38][39] Because of these distinctive properties,t his radical system enables in situ quantitative evaluation of polymer chain scission through electron paramagnetic spectroscopic (EPR) studies,u nlike previously reported mechanophores. [31,32] These studies suggest that freezing polymer solutions does not generate polymer chain scission but conformational changes.T herefore,w hether freezing polymer solutions actually induces mechanical force along the polymer chains and if so,t he magnitude of the force generated, remains unclear.…”
mentioning
confidence: 99%
“…[12] Recently, Scaiano and co-workers introduced a new class of "radically different antioxidants". [13] These compounds, instead of being H-atom donors as the common antioxidants, thermally dissociate into carbon-centered radicals, thus taking advantage of the high rates of radical-radical reactions for the antioxidative activity.…”
mentioning
confidence: 99%
“…That could be an explanation why only the meso dimer is experimentally obtained and why dynamical equilibrium promotes carbon‐centered radicals to combine, leading to higher reaction rates than other reactions . This result is particularly interesting since DABBF, a well‐known molecule, has been studied as an antioxidant . In consequence, the persistent radical effect reinforces broad applicability in the self‐healing materials area, where resistance to oxygen reaction (autoxidation) is essential.…”
Section: Resultsmentioning
confidence: 91%